Ultrastructural characteristics of spermiogenesis in the domestic duck (Anas platyrhynchos) - Simões, K.; Orsi, A. M. [UNESP]; Viegas, K. A S (Wiley, 2005)
In this present study was observed that the spermatids underwent morphological differentiation and modifications, which primarily comprised nuclear elongation, during the process of spermiogenesis in the domestic duck. The acrosome was formed and the flagellum developed concomitantly with nuclear modifications. Thus, various modifications could be observed during this process, especially changes in the distribution of cytoplasmic organelles. Long cisternae of the rough endoplasmic reticulum present in the spermatid cytoplasm dissociated into vesicles and the distal centriole initiated the development of the flagellum in the cellular portion opposite to the acrosome. The ultrastructure of the spermatids of the domestic duck did not show the characteristic development of pre-acrosomal granules, but the acrosomal granule could be directly visualized in this species. © 2005 Blackwell Verlag.
Keywords: Anas platyrhynchos; animal; animal disease; cytoplasm; duck; electron microscopy; male; physiology; spermatid; spermatogenesis; ultrastructure; Animals; Cytoplasm; Ducks; Male; Microscopy, Electron; Spermatids; Spermatogenesis